Implantação de um modelo de gestão da qualidade no processo produtivo em panificadora do município de Fortaleza - Costa, Ana Maria Mac-Dowell (2004)
This work had as objective evaluate the effect of a system's implantation improvement of the hygienic-sanitary quality in a bakery at the Fortaleza's city, during a period of six months, using as tools: the 5S Program, Good Manufacture Practical (GMP), Standardized Operational Procedures (SOPs) and training. For such job, was made an initial diagnosis, using two forms, one to characterize the company and investigate if the company applies some tool of the quality and one other tracing the profile of the company front the GMP. The research had as focus, the bakery's sectors and packing, in which had been carried through microbiological analyses.The microbiological tests had been applied in 80 of the manipulator's workers in which had made the research of fecal coliform, though the method of the Multiplo Number Provable (MNP) and presence and absence of the Staphylococcus aureus; eleven samples between equipmenVutensil, where if they had made the research Standard Plate Counts (SPC), fecal coliform (MNP), absence and presence of Staphylococcus aureus and Bacillus cereus; in products like roll (carioquinha), hamburger bread, white bread and bread crumbs had been made the researches of fecal coliform (NMP) and Setmonelte spp.; and at was checked out the potability of the water in accordance of edict 518/2004. Had beÉm corrected and implanted the Manual of GMP and SOPs, was been instituted the 5S Proqrarn which ali the members of the organization had been involved and had been gave 40 hours of training and always made meetings if it was necessary. As a result, it had a very sensitive improvement in the sanitary hygienic profile of the workers manipulators, equipmenVutensil and products although has not reached the percentage of 100. The most of the improvements had been made at the procedures and small investments. The main conclusion of this study was that a period of six months is insufficient to implant properly a hygienic-sanitary system of quality which had the need more time for physical structure improvement, layout and old pattems of ali workers manipulators' food in a company. The 5S program is an essential tool to remain GMP and the SOPs is an excellent tool to manage the quality in the routine of food services.